Brazil nut harvesting in Peruvian Amazonia from the perspective of ecosystem services - Risto Kalliola; Pedro Flores (Fennia: International Journal of Geography, 2011)
Brazil nuts are harvested from the primary rainforests in the Amazonian lowlands as a direct form of sustainably using the region’s biological resources. We analyze the ecological economics of Brazil nut production in the Peruvian region of Madre de Dios where nut extraction occurs on hundreds of small-holder concessions operating under long-term agreements. This activity sustains locally important economies that suffer from small volumes and high seasonality. The size and the remoteness of the NTFP concession determine much of its profitability to concessionaires. Seasonality of the harvest generates short-term income peaks for the majority of collectors. The fragility of the Brazil nut economy in the region is compounded by volatile market prices and the overall development pressures in Amazonia, which usually involve deforestation. Although the current regulatory mechanisms in Peru encourage long-term Brazil nut production in concessions, the income level is seldom high enough to help concession-owners to rise from poverty. Auxiliary financial support based on compensations for the non-valued ecosystem services provided by the forest-covered Brazil nut concessions could change the picture. Funds for these could come from international instruments like those of carbon emission control or debt for nature swaps. Green marketing could be developed to consider payments supporting ecosystem values as well as mechanisms supporting indigenous communities working with Brazil nuts. Appropriate indicators are needed to optimize those management, policy and trading conditions that best help to preserve the invaluable ecosystem functions and services.